The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1989
DOI: 10.1007/bf01646880
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of hepatitis A and B in norwegian merchant seamen — A serological study

Abstract: The prevalence of viral hepatitis in Norwegian merchant seamen in overseas trade was studied in 523 volunteers during compulsory health control before embarkation from the port of Oslo. The prevalence of hepatitis B markers was 9.4%, which is significantly higher than in the general Norwegian population. The prevalence increased with the number of years of occupation. It was associated with frequent casual sexual contacts in foreign countries, but not significantly increased in participants who had been expose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1990
1990
2002
2002

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Some cross-sectional and case-control studies have detected an association between tattooing and HBV [10][11][12][13][14][15][16][17], HCV [18][19][20][21][22][23][24][25][26][27] and HIV [28] infections. However, such associations were not demonstrated in other studies on HBV [29][30][31][32], HCV [17,[33][34][35][36][37], and HIV (38) infections. The studies that found an association between tattooing and these infections * Author for correspondence.…”
Section: Introductionmentioning
confidence: 58%
“…Some cross-sectional and case-control studies have detected an association between tattooing and HBV [10][11][12][13][14][15][16][17], HCV [18][19][20][21][22][23][24][25][26][27] and HIV [28] infections. However, such associations were not demonstrated in other studies on HBV [29][30][31][32], HCV [17,[33][34][35][36][37], and HIV (38) infections. The studies that found an association between tattooing and these infections * Author for correspondence.…”
Section: Introductionmentioning
confidence: 58%
“…4 In other studies too, an association between sexual contacts abroad and HBV markers was found. 5,[17][18][19] We demonstrated that, of those in the medical profession, physicians had a higher risk for HBV infection than nurses. Other studies demonstrated a high risk of infection for expatriates in the medical profession, but did not reveal a difference in risk between physicians and nurses.…”
Section: Discussionmentioning
confidence: 92%
“…Several epidemiological studies have shown an association between tattooing and HBV [23][24][25][26][27][28][29][30], HCV [31][32][33][34][35][36][37][38][39][40] and HIV [41] infections. Other studies, however, have not shown or were unable to demonstrate such an association [30,[42][43][44][45][46][47][48][49][50][51]. Tattoos have also been associated with drug abuse and incarceration [52,53], which are also risk factors for several TTDs.…”
mentioning
confidence: 99%